Discrete element simulations and experiments of soil-winged subsoiler interaction - Wang, Xuezhen; Li, Peng; He, Jinpu; Wei, Wuquan; Huang, Yuxiang (International Journal of Agricultural and Biological Engineering, 2021)
Understanding soil disturbance behaviors under the impact of the winged subsoiler is critical for designing or optimizing the winged subsoiler (a primary subsoiling tool). In this study, a soil-winged subsoiler interaction model was developed and the effects of winged subsoiler on soil disturbance behaviors were investigated using the discrete element method (DEM) simulations and lab soil-bin tests. The results showed that wings mainly affected the disturbance range and fragmentation degree of soil above them. The draught forces of share section (SS), arc section in the hardpan (ASHP), arc section in the top layer (ASTL) and line section (LS) were accounted for 69.53%, 25.22%, 4.73% and 0.52% of the total draught force of winged subsoiler; the lateral disturbance range from high to low of the soil at different depths followed the ranking: top layer (TL), hardpan disturbed by arc section (HDAS) and hardpan disturbed by share section (HDSS). Wings had the greatest influence on the draught force of ASHP. Adding wings to an arc-shaped subsoiler increased the disturbance areas of HDAS, TL and HDSS by 47.52%, 7.74% and 4.59%, respectively, but meanwhile increased the total draught force by 36%. Compared with a non-winged subsoiler, winged subsoiler had higher soil looseness (15.83%), soil disturbance coefficient (58.59%), furrow width (448.65 mm) and soil disturbance area ratio (0.3835), but poorer soil surface flatness (19.79 mm) and lower soil loosening efficiency (39.35 mm²/N). This study provided critical information for optimizing winged subsoilers on aspects of improving soil loosening effectiveness and reducing draught force.Keywords: hardpan, winged subsoiler, draught force, soil disturbance, discrete element method (DEM), experimentDOI: 10.25165/j.ijabe.20211401.5447Citation: Wang X Z, Li P, He J P, Wei W Q, Huang Y X. Discrete element simulations and experiments of soil-winged subsoiler interaction. Int J Agric & Biol Eng, 2021; 14(1): 50–62.